Knowledge Sharing, Psychological Empowerment and Lecturer Performance at UBP Karawang Campus: A Survey - Enjang Suherman; Suroso; Citra Savitri (Jurnal Mantik, 2022)
The Covid-19 pandemic has changed the work pattern of lecturers, which has an impact on the performance of the tridharma of lecturers' universities. Lecturers rely on individual abilities, psychological encouragement, and determine development in completing a job, this is psychological empowerment. Sharing knowledge of lecturers will produce new knowledge so that lecturers are able to make changes. However, not all lecturers want to share their knowledge and not all lecturers have the motivation to explore information or knowledge from other lecturers. UBP Karawang is a newly established university and has great potential to develop with all its shortcomings. The purpose of this study is to analyze and describe knowledge sharing, psychological empowerment and performance of UBP Karawang lecturers. This research method uses a descriptive design while the research method is a survey and literature study. The research data uses primary and secondary data from lecturer interviews while secondary data is a literature review. The data analysis technique used descriptive analysis. The results showed that knowledge sharing activities were seen from the perspective of individual factors, technology and organizational factors. The psychological empowerment activities of lecturers are also good, this is because they are proud to be lecturers, have a sense of competence, a sense of influence, and a sense of work autonomy. And the results of the lecturer's performance have been going well, including learning activities, service, and research.